Development of a Web-Based and Mobile Psychological Consultation Queue Service at DP3AKB Balikpapan with API - Ihsan; Sari, Danar Retno; Armin; Aditya, Angga Wahyu; Zulkarnain; Irawan, Candra (Jurnal Teknologi dan Manajemen Informatika, 2025)
The increasing demand for effective public services necessitates a more efficient queue management system. This study aims to design and implement a real-time online queue application for web and mobile platforms, using the Django and Flutter frameworks, and integrating Application Programming Interfaces (APIs) as a bridge between the two platforms. The methodology applied is software engineering with a case study approach at Puspaga Harapan, Balikpapan City. The system design includes digitizing the registration, validation, consultation scheduling, and psychological reporting stages. The developed application enables users to register independently and provides administrators and psychologists with real-time access to manage client data through a responsive and secure interface. The results of the study, based on 19 respondents who assessed 15 questions via a Likert scale questionnaire, with an average percentage of 94.73%, indicate very satisfactory results. This suggests that the system improves service efficiency, speeds up the registration and consultation process, and produces more accurate report data. The development of this system can overcome various obstacles from manual systems and support digital transformation in psychological consultation services.